Kualitas Kandungan Gizi Dadih Susu Kerbau Dengan Perbedaan Lama Waktu Penyimpanan Beku - Dara Surtina; Alfian Asri; , Harissatria; John Hendri; Delsi Afrini; Edi Firnando; Ranza Nofisra Gustaf; Hasan, Muhammad Ilham (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2025)
Buffalo milk fermented into curd is one of the functional foods because it contains Lactic Acid Bacteria (LAB) as probiotic bacteria that are very beneficial for body health that have been processed and consumed by the Minang people since ancient times. The purpose of this study was to test the nutritional content of buffalo milk curd, namely the pH value, protein content, fat content, and total colonies of buffalo milk curd bacteria stored in the freezer with different storage periods. The method used in this study was an experiment using a Completely Randomized Design (CRD) with 4 treatments, namely without storage of curd, frozen storage for 7 days, 14 days and 21 days. The results showed that the effect of the frozen storage period of buffalo milk curd in the freezer had a very significant effect (P <0.01) on the pH value of buffalo milk curd, protein content of buffalo milk curd, fat of buffalo milk curd and total colonies of buffalo milk curd bacteria. While in the content of organic matter and dry matter there was no significant difference.